A Comparative Study of Language Learning Strategies Used by Monolingual and Bilingual Learners - Ahmet Yayla; Ishak Kozikoglu; Sehnaz Nigar Celik (European Scientific Journal, ESJ, 2016)
The purpose of this research is to analyze monolingual and bilingual university students’ language learning strategies (LLS) comparatively and to determine whether students’ level of using language learning strategies in foreign language learning process changes in terms of variables such as gender, department and school type. This research was conducted among 524 university students at Yüzüncü Yıl University and Bülent Ecevit University Çaycuma Vocational School. Data of the study was collected by “Strategy Inventory of Language Learning” developed by Oxford (1990) and adapted into Turkish by Cesur and Fer (2007). Data collected was analyzed with descriptive statistics and parametric tests. As a result of the research, it was found that bilingual students use language learning strategies in foreign language learning process more than monolingual students. Furthermore, it was found that university students use language learning strategies at middle level; students mostly use metacognitive strategies and use affective strategies the least; female students use language learning strategies more than male students except cognitive and affective strategies; English language and literature and English language teaching department students use language learning strategies more than department of translation students; 4 years faculty students use language learning strategies more than vocational school students.